Patterns of methamphetamine use and symptoms of depression among young adults in northern Thailand - Catherine G. Sutcliffe (2018)
Introduction: Depression often co-occurs with amphetamine type stimulant use and can negatively impact drug treatment outcomes. Understanding the temporal relationship between depressive symptoms and methamphetamine use can further inform both treatment and mental health options. Methods: Methamphetamine users aged 18-25 years were enrolled in a 12-month randomized behavioral trial in Thailand. Questionnaires were administered every 3 months and included information on substance use and depressive symptoms. Pattern of methamphetamine use during follow-up was characterized into four groups: early cessation, late cessation, relapse and persistent use. Multinomial logistic regression was used to determine the impact of baseline depressive symptoms (CES-D score and % ≥22) on patterns of methamphetamine use during follow-up. Linear and logistic regression was used to determine the impact of patterns of methamphetamine use on depressive symptoms at the end of the trial. Results: No association was found between baseline depressive symptoms and subsequent patterns of methamphetamine use. A significant relationship was found between patterns of methamphetamine use and ensuing depressive symptoms, with those achieving cessation experiencing lower levels of depressive symptoms. Discussion: Many symptoms of depression may resolve with cessation or reduction in methamphetamine use. Clinical and community-based efforts that facilitate drug users' attempts to stop using drugs should be supported as they may contribute to positive cessation outcomes and help to improve overall mental health. © 2009 Elsevier Ireland Ltd. All rights reserved.